DAMPAK PENGUMUMAN PPATK TERHADAP KEPUTUSAN INVESTOR: ANALISIS REAKSI PASAR SAHAM PERBANKAN - Wigantini, Ghea Revina; Fadilah, Muhammad Ikhsan (JURNAL LENTERA BISNIS, 2026)
Stock price movements in the capital market are highly influenced by information, including government policies related to financial transaction monitoring. This study analyzes the reaction of the Indonesian capital market to the announcement of the policy on blocking inactive (dormant) bank accounts issued by the Indonesian Financial Transaction Reports and Analysis Center (PPATK) on July 28, 2025. Using an event study approach, the research examines whether abnormal returns occurred in banking stocks in response to the announcement. The sample consists of 44 banking stocks listed on the Indonesia Stock Exchange. Abnormal returns were calculated using the Market-Adjusted Model with two market proxies: the IHSG as a general market index and IDXFinance as a sectoral financial index. The results indicate significant market reactions both before and after the announcement date. These findings confirm that Indonesia’s financial market is sensitive to regulatory information that directly affects the banking industry, while also revealing differences in reaction patterns between the general market and the financial sector. This study provides important implications for regulators, market participants, and banking management regarding the role of information transparency and strengthened governance in maintaining market stability.